PENGELOLAAN INFORMASI PENYELENGGARAAN CONFERENCE TERPADU DI UIN AR-RANIRY BANDA ACEH DENGAN APLIKASI OPEN CONFERENCE SYSTEM (OCS) - Rahmad Ade Akbar; Bustami Yusuf; Masrura Mailany (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2019)
This research was motivated by information media in holding a conference at UIN Ar-Raniry which was considered to be still less effective in disseminating conference information to be held. Information on organizing conferences in UIN Ar-Raniry is not integrated in one system or is still distributed separately. The application of the Open conference system (OCS) as an integrated media for organizing conference information in UIN Ar-Raniry is expected to have a very good impact. Open Conference System (OCS) is an open source Content Management System (CMS) created by the Public Knowledge Project (PKP) and developed again by researchers using the Research and Development (RnD) method with the Extreme Programming development method. The results of the development of this system are tested using the User Acceptance Test (UAT) method that uses the Linkert technique as the scale. This test involved 38 respondents from 19 study programs throughout the faculties at Ar-Raniry UIN. The test results obtained an average value of 4.04 with a percentage of 80.8% which means that respondents strongly agree with the system developed.